Genetic diversity, evolution and drug resistance of Mycobacterium tuberculosis lineage 2 - Atavliyeva, Sabina; Auganova, Dana; Tarlykov, Pavel (Frontiers in Microbiology, 2024)
Mycobacterium tuberculosis causes a chronic infectious disease called tuberculosis. Phylogenetic lineage 2 (L2) of M. tuberculosis, also known as the East Asian lineage, is associated with high virulence, increased transmissibility, and the spread of multidrug-resistant strains. This review article examines the genomic characteristics of the M. tuberculosis genome and M. tuberculosis lineage 2, such as the unique insertion sequence and spoligotype patterns, as well as MIRU-VNTR typing, and SNP-based barcoding. The review describes the geographical distribution of lineage 2 and its history of origin. In addition, the article discusses recent studies on drug resistance and compensatory mechanisms of M. tuberculosis lineage 2 and its impact on the pathogen’s transmissibility and virulence. This review article discusses the importance of establishing a unified classification for lineage 2 to ensure consistency in terminology and criteria across different studies and settings.